2013
DOI: 10.1080/00224545.2013.843501
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Associations Between Contingent Self-Worth and Aspirations Among Iranian University Students

Abstract: This study investigated the novel associations between intrinsic and extrinsic aspirations and internal and external domains of contingent self-worth among a sample of 502 Iranian university students. We found a meaningful pattern showing that intrinsic aspirations were positively associated with internal domains, whereas extrinsic aspirations were positively associated with external domains. Our survey data also suggested that the factor structure of the Aspiration Index, as well as the factor structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Often, when people rate their extrinsic aspirations as likely or as already accomplished (as compared to rating them as important), the associations with wellness continue to be negative or very weakly positive (Frost, 1997; Raj & Chettiar, 2012; Stevens et al, 2011), especially when relative centrality indices of extrinsic aspirations are used (Brown et al, 2009; Frost & Frost, 2000; Kasser, 1996; Kasser & Ahuvia, 2002; Kasser & Ryan, 1993, 1996). However, several studies reported small-to-moderately sized positive effects between likely or already-attained extrinsic goals and wellness (Górnik-Durose & Pyszkowska, 2020; Romero et al, 2012; Sabzehara et al, 2014; Tóth et al, 2018). Perhaps most decisive was Niemiec et al’s (2009) classic longitudinal finding that intrinsically and extrinsically goal-oriented college students were equally likely to have achieved their goals after 2 years.…”
Section: Intrinsic and Extrinsic Aspirations And Wellnessmentioning
confidence: 99%
“…Often, when people rate their extrinsic aspirations as likely or as already accomplished (as compared to rating them as important), the associations with wellness continue to be negative or very weakly positive (Frost, 1997; Raj & Chettiar, 2012; Stevens et al, 2011), especially when relative centrality indices of extrinsic aspirations are used (Brown et al, 2009; Frost & Frost, 2000; Kasser, 1996; Kasser & Ahuvia, 2002; Kasser & Ryan, 1993, 1996). However, several studies reported small-to-moderately sized positive effects between likely or already-attained extrinsic goals and wellness (Górnik-Durose & Pyszkowska, 2020; Romero et al, 2012; Sabzehara et al, 2014; Tóth et al, 2018). Perhaps most decisive was Niemiec et al’s (2009) classic longitudinal finding that intrinsically and extrinsically goal-oriented college students were equally likely to have achieved their goals after 2 years.…”
Section: Intrinsic and Extrinsic Aspirations And Wellnessmentioning
confidence: 99%
“…For each individual these seven scores could then be ranked so that the aspirations with the highest scores could be deemed that individual's main aspirations. The AI has been shown to be valid and reliable in 15 different cultures (Grouzet et al, 2005) and has been frequently used in psychology research (Konkolÿ Thege et al, 2009;Niemiec et al, 2009;Sabzehara et al, 2014;Steffen, 2014).…”
Section: The Aimentioning
confidence: 99%
“…The intrinsic aspirations examined in past studies typically include affiliation (having deep, enduring relationships), community contribution (generativity and helping others), personal growth (self-acceptance and development), and physical health , whereas typical extrinsic aspirations have included financial success and wealth, popularity (being famous or admired), and having an appealing image (being physically attractive) (e.g., Kasser and Ryan, 1996; Niemiec et al, 2009). These seven specific aspirations are most often located within their respective higher-order intrinsic and extrinsic domains using factor analysis (Kasser and Ryan, 1996; SabzehAra et al, 2014). However, such analyses preclude a more fine-grain discussion about how the specific aspirations are associated with each other, both within and between the higher-order categories.…”
Section: Introductionmentioning
confidence: 99%